A diastereoselective synthesis of cyclopentanones via photocatalytic reductive alkyltrifluoromethylation of ynones. Issue 20 (30th August 2022) - Qiu, Jiayan; Le, Siya; Su, Jingwen; Liu, Yi; Zhou, Yulu; Zheng, Hanliang; Bai, Yihui; Zhu, Gangguo
Abstract : A photocatalytic reductive alkyltrifluoromethylation of ynones with the Langlois reagent is developed, providing a regio- and diastereoselective access to trifluoromethylated cyclopentanones under mild conditions. Abstract : Traditional alkyne carbotrifluoromethylation protocols lead to the production of trifluoromethylated alkenes, while new reaction modes remain to be explored. Herein, a visible light induced reductive alkyltrifluoromethylation of ynones with the Langlois reagent is developed, providing a regio- and diastereoselective access to highly functionalized trifluoromethylated cyclopentanones at room temperature. Mechanistic studies suggest a radical pathway involving the regioselective trifluoromethylation of C–C triple bonds, 1, 5-HAT, 5- endo-trig closure, single electron transfer reduction, and protonation.